MENGHADAPI PERSAINGAN PENYELENGGARA IBADAH HAJI KHUSUS (PIHK) DAN PENYELENGGARA PERJALANAN IBADAH UMRAH (PPIU) DI KALIMANTAN SELATAN MELALUI STRATEGI SIKLUS HIDUP PRODUK - Noviyanti, Devi (Alhadharah: Jurnal Ilmu Dakwah, 2019)
As country with majority population of Muslims, Indonesia has provided a great opportunity for Organizers of the Special Hajj Worship (Penyelenggara Ibadah Haji Khusus-PIHK) and Organizers of the Umrah Worship Tour (Penyelenggara Perjalanan Ibadah Umrah-PPIU) to serve the people that want to departing the Hajj in a faster time. This opportunity because of the high interest of the Indonesian people to perform the Hajj worship, which has led to the long waiting of period for the Hajj worship through the regular Hajj. The province of South Kalimantan, which is the one of province with the third longest regular hajj waiting period time, provides extensive potential for PIHK and PPIU to carry out activities in order to provide services for special hajj and umrah. Therefore, it is important to do various strategies by PIHK and PPIU in South Kalimantan in the face of competition, one of them is through the product life cycle strategy (product life cycle)